Sharing administrative health data with private industry: A report on two citizens' juries. (28th May 2021) - Street, Jackie; Fabrianesi, Belinda; Adams, Carolyn; Flack, Felicity; Smith, Merran; Carter, Stacy M.; Lybrand, Sean; Brown, Anthony; Joyner, Serena; Mullan, Judy; Lago, Luise; Carolan, Lucy; et al.
Abstract: Background: There is good evidence of both community support for sharing public sector administrative health data in the public interest and concern about data security, misuse and loss of control over health information, particularly if private sector organizations are the data recipients. To date, there is little research describing the perspectives of informed community members on private sector use of public health data and, particularly, on the conditions under which that use might be justified. Methods: Two citizens' juries were held in February 2020 in two locations close to Sydney, Australia. Jurors considered the charge: 'Under what circumstances is it permissible for governments to share health data with private industry for research and development?' Results: All jurors, bar one, in principle supported sharing government administrative health data with private industry for research and development. The support was conditional and the juries' recommendations specifying these conditions related closely to the concerns they identified in deliberation. Conclusion: The outcomes of the deliberative processes suggest that informed Australian citizens are willing to accept sharing their administrative health data, including with private industry, providing the intended purpose is clearly of public benefit, sharing occurs responsibly in a framework of accountability, and the data are securely held. Patient and Public Contribution: The design of the jury was guided by an Advisory Group including representatives from a health consumer organization. The jurors themselves were selected to be descriptively representative of their communities and with independent facilitation wrote the recommendations.